Effectiveness of discussion room's reservation service: Ez-BP PSB / Noor Azlin Abdullah ... [et al.] - Abdullah, Noor Azlin; Zainol, Mohd Amin; Ahmad, Mazuriah; Baharom, Mat Asri; Che Oon, Norismaliza (Universiti Teknologi MARA, Kedah, 2019)
Objectives of this invention is to expand the effectiveness in booking process from manual to database system through Ez-BP at Perpustakaan Sultan Badlishah UiTM (PSB) Kedah. In order to sustain and shared the new invention, PSB served and provided the reservation for discussion room to end user especially student in a short time which is cover the Surging Ahead Through Creativity. The culture of invention will prepare us to innovate and try to commercialize. The novelty and the uniqueness of Ez-BP are affected to the technologies usage and the implementation will carry out a platform which is more easily, full of integrity that’s related to end user (reduce bias's issue and highly fairness). This invention can get immediate feedback. “Ez-BP” provide the great impact by saving times, reduces budget for paper and system, implement green environment (paperless) and also provided the original data because it’s cannot be altered. Commercialization aspect that could be consider is to offer the consultation’s services for build up this booking platform thought out the academic lifestyle that affected to student and culture. The inventions of the flow in reservation’s process always looks simple but without an invention or creativity, the implementation and the process will be routine and manually. There will no relationship among workflow and the invention or new technologies involve especially in academic fields. So, as a conclusion, this invention of Ez-BP was really needed because we need the learning process that can contribute to the novelty and uniqueness as mentioned.